Demographic and Socioeconomic Influences Shaping Usage of Online Channel for Purchase of Food & Grocery - Prasad, Sarita; Sharma, Mukund (Indian Journal of Marketing, 2016)
The tug-of-war between the physical and online stores has intensified in recent years with an exponential growth in Internet usage and a subsequent boost to online shopping. Consequently, the retail industry is going through a disruptive phase, and the crux of all these disruptions is the change in the channel usage and preferences of the buyers. The adoption and usage of online channels by the buyers has been different for different product categories. In order to realize the market potential of online food & grocery retail, it is necessary to understand the buyers’ characteristics that impact the online channel usage for purchase of food & grocery. The objective of the study was to understand the influence of demographic and socioeconomic factors among the Indian populace on online channel usage and non-usage for purchase of food & grocery. The study is based on an empirical analysis of the profile of buyers of food & grocery in Bangalore, India. The findings in the context of the Indian urban population revealed that demographic factors do not impact online channel usage for food & grocery purchase. The study showed that socioeconomic factors, pertaining to the respondent buyer, did have a significant impact ; whereas those pertaining to the chief wage earner in the household did not impact the online channel usage. The marketing implications for the online retailers suggest that for increased market penetration, a communication strategy focused on bringing an attitudinal change among the chief wage earners is needed in those households that do not purchase food & grocery online.